A survey of research on the book of Lamentations - Gous, Ignatius G. P. (Old Testament essays, 1992)
In a sense, the purpose of this research survey matches that of the book of Lamentations, which it is about. Both are a quest for order in a world full of contradictions. One of the most debated questions regarding this book is about the author. The author of the article is, to his knowledge, the only researcher who believes that the poets remained adherents of the theology of Zion. The article also focuses on the structure and flow of thoughts of the poems, on the genre, dating, and acrostic form; on how Lamentations originated and developed, and the tracing of ideas in subsequent times.